Jarcho-Levin Syndrome Associated With Anorectal Malformation: A Rare Case Report - Okvita Wiyogo, Illona; Hariastawa, IGB Adria (Journal of Neonatal Surgery, 2025)
Introduction: Jarcho-Levin syndrome is a congenital disorder characterized most commonly by the presence of rib and vertebral defects at birth. The association with other organs such as the spinal, brain, and the urinary system has been reported. The paper reports a rare case of Jarcho-Levin syndrome associated anorectal malformation. Case presentation: The case is a full-term boy which had a short neck with an undefined chest deformity and protuberant abdomen. He did not pass any stool since birth and had no anal opening. Early identification and management is crucial for optimal outcomes. Conclusion: The paper reports a rare case of Jarcho-Levin syndrome associated with anorectal malformation. Early screening and diagnosis is important to determine further management.